Contribution of genetic factors to neonatal transient hypothyroidism. Issue 1 (21st December 2004) - Niu, D-M; Lin, C-Y; Hwang, B; Jap, T-S; Liao, C-J; Wu, J-Y
Abstract : Background: The causes of neonatal transient hypothyroidism (NTH) remain incompletely understood. Whether it is influenced by genetic background is rarely discussed and remains unproven. A defect in thyroid peroxidase is a common cause of dyshormonogenesis of the thyroid gland in Taiwanese, with a novel mutation (2268insT) present in nearly 90% of alleles studied. Objective: To determine if the presence of this common mutation is associated with NTH in Taiwan. Methods: A mismatched primer was designed and used for this specific 2268insT mutation to screen 1000 normal babies and 260 babies with confirmed NTH. Results: The carrier rate for 2268insT in normal babies (1/200) was significantly lower than in babies with NTH (1/13; p<0.0001). Conclusions: The results strongly suggest that the presence of this thyroid peroxidase mutation contributes to the development of NTH. Likely pathogenetic explanations include the effect of the stress of extrauterine adaptation during labour on an immature pituitary-thyroid axis in genetically predisposed individuals, combined with environmental triggers such as iodine deficiency, perinatal iodine exposure, and/or goitrogen contamination.